Associação entre o modelo seleção, otimização e compensação e a depressão em idosos - Nathalya Aparecida Rocha Alves Cruz (2019)
The Selection, Optimization and Compensation (SOC) model presents strategies for the regulation of losses throughout life and coping with normative and non-normative changes. The selection refers to the reduction of alternatives and reorganization of goals. Optimization involves the management, acquisition, and maintenance of resources to achieve higher levels of operation. Compensation is associated with the adoption of alternative behaviors or resources to alleviate losses or maintain performance. The main objective of this dissertation was to analyze the effect of the use of SOC strategies on the depressive symptoms of the elderly in front of stressful events. The first session of the dissertation presents an integrative review about the SOC model, evaluating the main outcomes related to the use of strategies in different phases of life. Then, an article is presented that discusses the association between the SOC model and depression. It has been observed that the use of SOC acts as an effect modifier in the relationship between stressors and depression. In addition, were observed that the odds of the elderly who presented low use of SOC resources presenting depression was 2.46 times higher than in the elderly who present high use of these resources. These results on the relationship between stress, SOC and depression in the elderly reinforce the relevance of the insertion of these strategies in studies and interventions on the subject, since their use can help promote well being, decrease depressive symptoms, improve coping with disease and work capacity. It is suggested that future investigations continue the study of the modifying effect of SOC and its implications on the emotional state of the elderly.